Online teaching and learning evaluation support system (TLESS) - Sim, Cheng Chong (Universiti Malaysia Sarawak, UNIMAS, 2005)
The Online Teaching and Learning Evaluation Support System (TLESS) is a web based system to manage the course, lecturer and tutor evaluation information and result effectively. This thesis discussed about the overview of the Teaching and Evaluation System, the background of the system, the methodology used, the system analysis process, system design process, system implementation process, testing and evaluation process and also the future works. The main features of this system are enable students to evaluate course, lecturer and tutor through online, manipulation of student, course and clerk record, generate report in text and pie chart format, print course, lecturer and tutor evaluation report. The details of these features will be discussed in this thesis. As a conclusion, TLESS achieved the goals.